Implementation of Business Intelligence for Hospital Performance Evaluation Based on Minimum Service Standards (SPM) at YK Madira Hospital Palembang - Tri Wahyudi (Institute of Information Technology and Social Science (IITSS), 2024)
The use of information technology has become a crucial component in hospital management to enhance operational effectiveness and service quality. However, at YK Madira Hospital Palembang, the Hospital Management Information System (SIMRS) currently serves only as a data entry and reporting tool, with data typically exported in Excel format, making it difficult for management to analyze information efficiently. This study aims to develop and implement a Business Intelligence (BI) system using Microsoft Power BI to evaluate hospital performance based on the Minimum Service Standards (SPM) established by the Ministry of Health (Kementerian Kesehatan) of the Republic of Indonesia. The SPM indicators analyzed include Bed Occupancy Rate (BOR), Average Length of Stay (ALOS), Bed Turn Over (BTO), Turn Over Interval (TOI), Net Death Rate (NDR), and Gross Death Rate (GDR). The research employed a quantitative descriptive approach, supported by data from 2017–2020 obtained from the hospital’s SIMRS. The system was designed through a data warehouse model and visualized using Power BI dashboards. The results demonstrate that the BI system enables dynamic visualization and analysis of hospital performance data, facilitating faster and more accurate decision-making. The study concludes that implementing BI significantly enhances the effectiveness of performance monitoring and compliance with the Ministry of Health’s service standards.